2006
DOI: 10.1007/s10479-006-0038-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the financial performance of bank branches

Abstract: We evaluate the financial performance of most of the branch offices of a large European savings bank for a recent accounting period. We employ a complementary pair of nonparametric techniques to evaluate their financial performance, in terms of their ability to conserve on the expenses they incur in building their customer bases and providing customer services. We find variation in the ability of branch offices to perform this task, and agreement on the identity of the laggard branches. We then employ parametr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Camanho and Dyson (2005b) analysed 144 branches of a Portuguese commercial bank and observed considerable inefficiencies in this network. Pastor et al (2006) used DEA to examine the profit efficiency of 573 branch offices of a large European savings bank and reported that efficiency improvements at the worst-performing branches (where savings of up to 45% in the use of resources could be obtained), would generate a substantial increase in profit for the bank. Regarding several dimensions, Oral and Yolalan (1990) assessed the profit and service efficiencies of 20 retail branches of a Turkish commercial bank, finding a positive relationship between these parameters, but that only 20% of the branches were efficient.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Camanho and Dyson (2005b) analysed 144 branches of a Portuguese commercial bank and observed considerable inefficiencies in this network. Pastor et al (2006) used DEA to examine the profit efficiency of 573 branch offices of a large European savings bank and reported that efficiency improvements at the worst-performing branches (where savings of up to 45% in the use of resources could be obtained), would generate a substantial increase in profit for the bank. Regarding several dimensions, Oral and Yolalan (1990) assessed the profit and service efficiencies of 20 retail branches of a Turkish commercial bank, finding a positive relationship between these parameters, but that only 20% of the branches were efficient.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, many articles have proposed more than one model with different variable combinations, thus further increasing the complexity of the analysis. Evolution of bank efficiency in Brazil: a DEA approach Liu (2010) Measuring and categorizing technical efficiency and productivity change of commercial banks in Taiwan Liu (2009) Slacks-based efficiency measures for predicting bank performance Tecles and Tabak (2010) Determinants of bank efficiency: the case of Brazil Hadad et al (2012) A new approach to dealing with negative numbers in efficiency analysis: an application to the Indonesian banking sector Kao and Liu (2009) Stochastic data envelopment analysis in measuring the efficiency of Taiwan commercial banks Tortosa-Ausina (2002a) Exploring efficiency differences over time in the Spanish banking industry Taylor et al (1997) DEA/AR efficiency and profitability of Mexican banks: a total income model Mester (1997) Measuring efficiency at US banks: accounting for heterogeneity is important Bos et al (2009) Effects of heterogeneity on bank efficiency scores Brissimis et al (2010) Technical and allocative efficiency in European banking Hasan et al (2012) A Cobb Douglas Stochastic Frontier Model on measuring domestic bank efficiency in Malaysia Asmild and Matthews (2012) Multi-directional efficiency analysis of efficiency patterns in Chinese banks 1997-2008 Lin et al (2009) Application of DEA in analyzing a bank's operating performance Paradi et al (2011) Two-stage evaluation of bank branch efficiency using data envelopment analysis Kao and Liu (2014) Multi-period efficiency measurement in data envelopment analysis: the case of Taiwanese commercial banks Athanassopoulos (1997) Service quality and operating efficiency synergies for management control in the provision of financial services: evidence from Greek bank branches Ray and Das (2010) Distribution of cost and profit efficiency: evidence from Indian banking Portela and Thanassoulis (2005) Profitability of a sample of Portuguese bank branches and its decomposition into technical and allocative components Wanke and Barros (2014) Two-stage DEA: an application to major Brazilian banks Bergendahl (1998) DEA and benchmarksan application to Nordic banks Siriopoulos and Tziogkidis (2010) How do Greek banking institutions react after significant events?a DEA approach Pastor et al (2006) Evaluating the financial performance of bank branches Wu et al (2006) Efficiency analysis of cross-region bank branches using fuzzy data envelopment analysis Saha and Ravisankar (2...…”
Section: Input and Output Handling And Categorizationmentioning
confidence: 99%
“…Girardone, Nankervis, and Velentza (2009) measured the operating efficiency of banks from 54 countries, including 15 EU countries. Pastor, Lovell, and Tulkens (2006) have studied profit efficiency of 573 branch offices of a European saving bank. Aggelopoulos et al (2010) studied both the production and profit efficiency of some branches of a large Greek bank.…”
Section: Efficiency Studies Using Data Envelopment Analysis (Dea)mentioning
confidence: 99%